(untitled) (Fiep Bulletin - online, 2013)
The objective of the present work was to study nutritional and biochemical parameters of female rats submitted to protein calorie malnutrition after birth and subsequent nutritional recovery, associated or not with physical exercise (swimming 30 minutes/day, 5 days/week during 8 weeks). 32 female Fisher rats were used which were divided into four groups: Sedentary Control (SC), Trained Control TC), Sedentary Recovered (SR) and Trained Recovered (TR). Food ingestion, weight gain and serum concentrations of total protein, albumin, hemoglobin and glucose were studied. It was observed that training produced increased food ingestion but without significant weight gain. Biochemical evaluation showed that the animals did not present nutritional recovery in the studied period and that training did not interfere in this process. The interaction between nutritional status and training for both food ingestion and serum glucose concentration signals the necessity of studying the present using other indicators of carbohydrate metabolism, for instance a glucose tolerance curve, besides of course other exercise models and even more intense exercise or a higher work volume.